Mechanical Properties of Direct Recycling Metal Matrix Composite (MMC-AlR) AA7075 Aircraft Aluminium Alloy - Yusuf, N.K.; Medi, A. S.; Lajis, M. A.; Chan, B. L.; Shamsudin, S. (International Journal of Integrated Engineering, 2021)
Recycling of aluminium aerospace alloys represents a major challenge to both the aluminium and aerospace industries. Ecological manageability in assembling is these days is a dire and exceptional issue and the principle concerns are identified with increasingly proficient utilization of energy and materials. Recycling allowed saving large amount greenhouse gas emission, particularly in the case of aluminium. Metal matrix composites spur the possibility of advancing typical monolithic material properties. Offering great strength, lightweight and being able to withstand high temperatures are the main behaviours of the metal matrix composite. To that extent, many practitioners in either automotive or aerospace industries employed metal matrix composite in most of the critical parts. Forming metal matrix composite via solid state processing is considered innovative, as most of the metal matrix composite forming process took place either in liquid or gaseous processing. An experimental investigation was conducted to investigate the mechanical properties of a recycled aluminium shifting alumina sum from 1 to 5 wt. % that had been presented to recycled aluminium chip employing hot press forging. Aluminium chip was obtained by milling AA7075-T1 bulk to a certain parameter. The medium size chips were cleaned, dried and mixed with alumina particles before being poured into a closed-die mould. The main responses investigated were ultimate tensile strength and elongation to failure and microstructure analysis. Out of all fractions, 4 wt. % of alumina shows the highest Ultimate tensile strength when the value increased from 155.214 MPa (1 wt. %) to 187.183 MPa. Further addition of alumina would enhance the composite strength, but in contrary, it also could prone the material performance.